Psychology of Religious Development in Students - Shofi, Putri (Jurnal Al-Fikrah, 2024)
This article is expected to provide understanding especially to educators about the development of religion in students that has an impact on the ease of implementing Islamic education. This article is The research method that the author uses in this study is qualitative research with library research. The results of the discussion of this article are There are two factors that influence the development of students, namely: (1) Heredity (inheritance) and (2) Environment. As for the development of religion in adults, they already have peace of mind, determination and firm beliefs in both positive and negative forms.